Organic matter distribution and fluxes within a holm oak (Quercus ilex L.) stand in the Etna volcano - LEONARDI, S; Rapp, M; DENES, A (Plant Ecology, 1992)
Located at 1100 m above sea level, on the western site of the Etna volcano, the ecophysiology of the Mount Minardo holm oak coppice has been investigated for more then twenty years. In this stand, now 31 years old, the above ground biomass amounts to 15000 g m 2 of organic material, including leaves and perennial woody material. During these 31 years, the mean annual production has been around 775 g m 2. The yearly mean litterfall amounts to 310 g m 2, including 200 g m -2 of leaves, mostly two years old. The soil surface is covered by a litter layer amounting to 3150 g m-2. Each year, following Jenny's decomposition rate and field measurements, 290 g m- 2 of the litter turns into CO2, or becomes incorporated in the soil organic matter.
Keywords: Mediterranean forests; organic matter cycling; Quercus ilex L

ORGANIC-MATTER DISTRIBUTION AND FLUXES WITHIN A HOLM OAK (QUERCUS-ILEX L) STAND IN THE ETNA VOLCANO - A SYNTHESIS - LEONARDI, S; Rapp, M; DENES, A (VEGETATIO, 1992)
Located at 1100 m above sea level, on the western site of the Etna volcano, the ecophysiology of the Mount Minardo holm oak coppice has been investigated for more then twenty years. In this stand, now 31 years old, the above ground biomass amounts to 15000 g m-2 of organic material, including leaves and perennial woody material. During these 31 years, the mean annual production has been around 775 g m-2. The yearly mean litterfall amounts to 310 g m-2, including 200 g m-2 of leaves, mostly two years old. The soil surface is covered by a litter layer amounting to 3150 g m-2. Each year, following Jenny's decomposition rate and field measurements, 290 g m-2 of the litter turns into CO2, or becomes incorporated in the soil organic matter.
Keywords: Mediterranean forests; ORGANIC MATER; QUERCUS-ILEX L

Productivity and nutrient uptake in a holm oak (Quercus ilex L.) stand and during regeneration after clearcut - Rapp, M; Derfoufi, F; Blanchard, A (Plant Ecology, 1992)
The effect of clearcutting on biomass production and nutrient consumption was examined during the two years in a clearcut and a mature Quercus ilex L. coppice. The comparison was limited to the leaf com- partment and to the annual shoots, which were the only con]parable compartments in the two situations. At the same time, the dynamics of the nutrient pool (N, P, K, Ca, Mg), monthly uptake and recycling from the foliage, were studied. The second year after cutting, the leaf production was roughly the same at the two sites. However, the photosynthates appear to be used differently: in the young stand the perennial wood production was greater than in the mature stand, where the maintenance costs are higher. This is corroborated by the patterns of nutrient use.
Keywords: biomass; Clearcut; coppice; nutrient use; production; Quercus ilex L.

BIOMASS PRODUCTION AND NUTRIENT REQUIREMENT DURING RESTORATION OF A HOLM OAK COPPICE - LEONARDI, S; Rapp, M (ACTA OECOLOGICA-INTERNATIONAL JOURNAL OF ECOLOGY, 1990)
The restoration of a holm oak (Quercus ilex L.) coppice was studied during three years following a clear-cut. Leaf area rebuilding, above-ground biomass production and nutrient requirement are especially studied. The new produced above-ground biomass amounts respectively to 151, 913 and 2 161 g m-2, one, two and three years after clear-cut. Leaf area index, at the same ages, amounts respectively to 0,3-1,9 and 4,4 m2/m2. The last value is nearly the same as those of the 30 year old coppice stand (4,4 m2/m2). The biomass increment corresponds to a current yearly above-ground productivity of 165, 748 and 1 248 g m-2 of fresh material during these three years. The mean annual above-ground production, calculated over thirty years, only amounts to 800 g m-2. Concerning nutrients, it seems that the early years are characterized by a higher requirement of nitrogen, phosphorus and potassium in comparison to the mature stand. The needs for calcium start to be important only after the third year, with the reappearance of ``stems{''} and later trunks.
Keywords: biomass; coppice; NUTRIENT REQUIREMENT; STAND RESTORATION

L'impact du déboisement sur l'azote minéral susceptible d'être absorbé par un taillis de chêne vert (Quercus ilex L) en reconstitution - Merzouki, A; Lossaint, P; Billes, G; Rapp, M (Ann. For. Sci., 1990)
The impact of deforestation on the mineral nitrogen available during restoration of the holm oak (Quercus ilex L) coppice. The impact of deforestation on the biological activity of a mediterranean red soil was studied from January 1984 to April 1986 within a holm oak (Quercus ilex L) stand after clearcut. Part of the study involved the estimation of the amount of nitrogen available for vegetation both in the mature holm oak coppice and in the 1-2-yr-old recovery stand. The study indicates that the new shoots essentially took up nitrate nitrogen; however, the mature site used both nitrate and ammonium nitrogen as nitrogen source. The availability of mineral nitrogen, essentially nitrate, ranged from 47.4 to 118.6 kg·ha -1·yr-1 in the rebuilding site and 25.6 to 63.9 kg·ha-1·yr-1 in the mature stand. At the control site, ammonium nitrogen represented 43% of the total nitrogen available.
Keywords: Deforestation; holm oak coppice; nitrate; nitrogen availability; Quercus ilex L; shoots

LITTER PRODUCTION AND MINERAL ELEMENT SUPPLY TO SOIL IN 2 MEDITERRANEAN ECOSYSTEMS - QUERCUS-ILEX FOREST AND QUERCUS-COCCIFERA GARRIGUE - Rapp, M (OECOLOGIA PLANTARUM, 1969)
APS
Keywords: LITTER PRODUCTION; Mediterranean ecosystems; minerals; Quercus coccifera; Quercus ilex

RETURN OF MINERAL ELEMENTS TO SOIL BY RAINWATER LEACHING CANOPIES OF QUERCUS ILEX L QUERCUS LANUGINOSA LAMK AND PINUS HALEPENSIS MILL WOODS - Rapp, M (OECOLOGIA PLANTARUM, 1969)
APS
Keywords: Pinus halepensis; Quercus ilex L.; Quercus lanuginosa; rainwater leaching